2010
DOI: 10.1111/j.1945-5100.2009.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ordinary chondrites using powder X-ray diffraction: 1. Modal mineral abundances

Abstract: Abstract-Powder X-ray diffraction (XRD) is used to quantify the modal abundances (in wt%) of 18 H, 17 L, and 13 LL unbrecciated ordinary chondrite falls, which represents the complete petrologic range of equilibrated ordinary chondrites (types 4-6). The XRD technique presents an effective alternative to traditional methods for determining modal abundances, such as optical point counting and electron microprobe phase (EMP) mapping. The majority of chondrite powders in this study were previously prepared for che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(144 citation statements)
references
References 17 publications
7
136
1
Order By: Relevance
“…We previously showed (Vernazza et al 2010) that the application of our model to the shorter near-IR range (0.8-2.5 μm instead of 0.4-2.5 μm) only increases the error in the ol/(ol+opx) ratio by 2%. Our model results are in agreement with measurements by independent techniques (Menzies et al 2005;Dunn et al 2010aDunn et al , 2010b; Mössbauer spectra, XRD). Our new spectral data ( Figure 1) indicate that the ol/(ol+low-Ca px) ratio is the same for type 3.0-3.4 OCs…”
Section: Compositional Analysis Of Our Meteorite and Asteroid Samplessupporting
confidence: 82%
See 3 more Smart Citations
“…We previously showed (Vernazza et al 2010) that the application of our model to the shorter near-IR range (0.8-2.5 μm instead of 0.4-2.5 μm) only increases the error in the ol/(ol+opx) ratio by 2%. Our model results are in agreement with measurements by independent techniques (Menzies et al 2005;Dunn et al 2010aDunn et al , 2010b; Mössbauer spectra, XRD). Our new spectral data ( Figure 1) indicate that the ol/(ol+low-Ca px) ratio is the same for type 3.0-3.4 OCs…”
Section: Compositional Analysis Of Our Meteorite and Asteroid Samplessupporting
confidence: 82%
“…In particular, the correlation may indicate that smaller H-like bodies formed with a more pyroxene-rich interior than larger H-like bodies (the data for families are in agreement with this hypothesis with Koronis members being on average more olivine-rich than Agnia or Merxia ones). In the context of the H4-H6 sequence (H4 < H5 < H6 in terms of ol/(ol+low-Ca px) ration; see Dunn et al 2010aDunn et al , 2010b this may imply that smaller bodies were formed with a higher fraction of H4 material while larger bodies formed with more H5 and/or H6 material. Thermal models (e.g., Henke et al 2012aHenke et al , 2012bHenke et al 2013) could directly test this hypothesis.…”
Section: A5 H Chondrite Parent Bodies: Correlation Between Size Andmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent presolar grain search showed that it has the highest matrix-normalized presolar silicate abundance of any chondrite (Nittler et al, 2013). Position sensitive detector X-ray diffraction (PSD-XRD) has proven to be a very useful tool both for determining bulk mineral abundances and for classification Menzies et al, 2005;Dunn et al, 2010;Howard et al, 2010Howard et al, , 2011Howard et al, 2015). Lastly, bulk O isotopes are an indispensable tool for classifying meteorites and for providing constraints on the influence of fluids during parent body processing (e.g., Clayton and Mayeda, 1999;Young et al, 1999;Greenwood and Franchi, 2004;Schrader et al, 2011).…”
Section: Introductionmentioning
confidence: 99%